Identification of WNT16 as a Predictable Biomarker for Accelerated Osteogenic Differentiation of Tonsil-Derived Mesenchymal Stem Cells In Vitro. (10th September 2019) - Kim, Yu-Hee; Cho, Kyung-Ah; Lee, Hyun-Ji; Park, Minhwa; Kim, Han Su; Park, Joo-Won; Woo, So-Youn; Ryu, Kyung-Ha
Abstract : The application of mesenchymal stem cells (MSCs) for treating bone-related diseases shows promising outcomes in preclinical studies. However, cells that are isolated and defined as MSCs comprise a heterogeneous population of progenitors. This heterogeneity can produce variations in the performance of MSCs, especially in applications that require differentiation potential in vivo, such as the treatment of osteoporosis. Here, we aimed to identify genetic markers in tonsil-derived MSCs (T-MSCs) that can predict osteogenic potential. Using a single-cell cloning method, we isolated and established several lines of nondifferentiating (ND) or osteoblast-prone (OP) clones. Next, we performed transcriptome sequencing of three ND and three OP clones that maintained the characteristics of MSCs and determined the top six genes that were upregulated in OP clones. Upregulation of WNT16 and DCLK1 expression was confirmed by real-time quantitative PCR, but only WNT16 expression was correlated with the osteogenic differentiation of T-MSCs from 10 different donors. Collectively, our findings suggest that WNT16 is a putative genetic marker that predicts the osteogenic potential of T-MSCs. Thus, examination of WNT16 expression as a selection criterion prior to the clinical application of MSCs may enhance the therapeutic efficacy of stem cell therapy for bone-related complications, including osteoporosis.